Analisis Kelayakan Pemasaran Produk Ikan Bumbu Kuning Dalam Kemasan Vacuum Berdasarkan Preferensi - Ragil Muhammad Husein; Riki Ahmad Maulana; Amirul Hakim Alfarizi; Isnaini Hasan Atsari (Business Finence Analyst Co.,, 2025)
This study aims to analyze the market feasibility of vacuum-packed ikan bumbu kuning products using the Food Choice Process approach, which includes three main components: life course, external influences, and personal food system. Data were collected through questionnaires distributed using an accidental sampling method, targeting respondents who were encountered directly and willing to participate. Data interpretation was conducted using a descriptive qualitative approach, examining response patterns for each variable. The results indicate that most respondents favor traditional Indonesian cuisine and prefer ready-to-eat meals due to their busy lifestyles. Factors such as price, packaging, product information, and ease of access also influence purchasing decisions. In terms of personal food evaluation, respondents consider practicality, health, quality, and taste. Therefore, vacuum-packed ikan bumbu kuning products are considered commercially viable, as they align well with consumer preferences.